Penguatan Kepedulian Sosial melalui Program Berbagi Sembako dan Alat Tulis di Panti Asuhan Peduli Yatim Bersama Makassar - Nur Isra' Ahmad; Supriadi; Mujahidah; Asyraf Mustamin; Nuraeni Gani (Jurusan Pendidikan Guru Sekolah Dasar Kampus VI Bone, 2026)
Orphans at the Makassar Orphanage Peduli Bersama Makassar still face limitations in meeting basic needs and educational facilities that have an impact on their learning motivationIn line with these problems, this service activity aims to provide basic necessities and stationery as an integrative effort that not only fosters social awareness, but also strengthens religious values and supports the sustainability of orphans' education. The community service method used is a participatory approach. The results of the activity showed that children not only felt materially helped, but also received stronger psychological encouragement and motivation to learn. Their enthusiasm when receiving stationery is clear evidence that simple support can have a big impact on the spirit of learning. This activity also shows that community service not only contributes to the fulfillment of basic needs, but also enriches the psychological and social aspects of orphans.